Handbook of research methods on intuition - Sinclair, Marta (Handbooks of research methods in management series, 2014)
How does one approach the study of intuition--a complex, cross-disciplinary field, which is still developing? How can intuition be captured in situ? How can researchers harness their own intuition? In this original Handbook, the expert collaborators use method-related themes to help answer these, and other questions, and explore innovative developments in intuition research. This groundbreaking Handbook is organized around six method-related themes: the question of cognitive systems and capabilities; the role of emotions and stress; major quantitative approaches; qualitative techniques for mapping intuition; the use of grounded theory; and the role of the researcher's own expertise and intuition. Academics and researchers of organizational behavior, as well as researchers in business and management, who use quantitative and qualitative research techniques, will find this book to be an informative and invaluable read. It will also be of interest to industry professionals looking to adopt new staff training and development methods